Significant roadblocks exist in developing sputum sample libraries for clinical validation of novel in vitro diagnostics - Dollow JM; Green JA (Dove Medical Press, 2014)
Joshua M Dollow, Justin A GreenGlaxoSmithKline, Uxbridge, UKAbstract: With the continuing rise of multiresistant pathogens, reliable, cost-effective, and novel diagnostics are urgently required by clinicians and clinical trialists to diagnose conditions such as respiratory tract infections to enable rational antimicrobial choice and enhance clinical outcomes. However, during product development, validation of these in vitro diagnostic devices, a key regulatory hurdle, requires sputum samples in large numbers. The Rapid Point-of-Care test Platform for Infectious Diseases (RAPP-ID) consortium is tasked with producing point of care test (POCT) platforms for rapid diagnosis of lower respiratory tract infections, including tuberculosis and blood stream infections. Validation of diagnostic platforms would ideally use well-characterized samples in a sputum library taken from a range of clinical settings to allow for a wide panel of pathogens to be assessed. These samples would be stored in specific stable conditions (monitored temperature, specific medium) until required for validation. Therefore we reviewed the current literature for details of storage conditions of sputum samples and for previous validation studies of other diagnostic tests using this methodology. However, we conclude that little data exists, and thus the acquisition and successful storage of good quality clinical samples are major roadblocks in the validation of novel POCT platforms, and that while not without limitations, spiked sputum samples appear the best solution until sputum library laboratory techniques allowing careful preservation of pathogens are improved.Keywords: sputum, storage, rapid diagnostic, respiratory tract infection